ANDROID BASED MOBILE ATTENDANCE SYSTEM APPLICATION ONLINE FOR ON SITE ENGINEERS AT PT. ZYX INDONESIA - Rasyiidin, Muhammad Yusuf Bagus (POLITEKNIK NEGERI JAKARTA, 2019)
As the development of technology almost everythingcan be done to use android, android is a linux-based operatingsystem with a system of opensoruce. To develop an androidapplication is also less because there have been many tools alreadyfull code or guide. PT. ZYX Indonesia on all Site engineers havealready complimented Android smartphone. Attendance Systemnow still use web base and need more time to do the attendance,such as the need to open the laptop, web browser login, enterthe page absent recently could do absent. In this case studyattendance system will be designed with the android application.On this application will facilitate engineer for absent because theuser interface is very easy, when directly connected to the logintimeout page attendance.